Players unleashed: modding the sims and the culture of gaming - Sihvonen, Tanja (MediaMatters, 2011)
It has been ten years since video game giant Electronic Arts first releasedThe Sims, the best-selling game that allows its players to create a household and then manage every aspect of daily life within it. And since its debut, gamers young and old have found ways to "mod"The Sims, a practice in which gamers manipulate the computer code of a game, and thereby alter it to add new content and scenarios. InPlayers Unleashed!-the first study of its kind-Tanja Sihvonen provides a fascinating examination of modding, tracing its evolution and detailing its impact onThe Simsand the game industry as a whole. Along the way, Sihvonen shares insights into specific modifications and the cultural contexts from which they emerge.